2017
DOI: 10.1128/jvi.01444-16
|View full text |Cite
|
Sign up to set email alerts
|

Interferon Regulatory Factor 1 and Type I Interferon Cooperate To Control Acute Gammaherpesvirus Infection

Abstract: Gammaherpesviruses are ubiquitous pathogens that establish lifelong infection in Ͼ95% of adults worldwide and are associated with a variety of malignancies. Coevolution of gammaherpesviruses with their hosts has resulted in an intricate relationship between the virus and the host immune system, and perturbation of the virus-host balance results in pathology. Interferon regulatory factor 1 (IRF-1) is a tumor suppressor that is also involved in the regulation of innate and adaptive immune responses. Here, we sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 41 publications
3
22
0
Order By: Relevance
“…4A and viral titers measured at 72h post infection. IFNγ treatment attenuated MHV68 replication in IFNAR −/− macrophages, albeit not to the same extent as that observed in type I IFN competent cultures, as we previously reported (Mboko et al, 2016). Specifically, ~50-fold increase of MHV68 titers above baseline was readily observed at 72 hours post infection of IFNγ-treated IFNAR deficient cells (Fig.…”
Section: Resultssupporting
confidence: 70%
See 2 more Smart Citations
“…4A and viral titers measured at 72h post infection. IFNγ treatment attenuated MHV68 replication in IFNAR −/− macrophages, albeit not to the same extent as that observed in type I IFN competent cultures, as we previously reported (Mboko et al, 2016). Specifically, ~50-fold increase of MHV68 titers above baseline was readily observed at 72 hours post infection of IFNγ-treated IFNAR deficient cells (Fig.…”
Section: Resultssupporting
confidence: 70%
“…Not surprisingly, IFNγ is a critical antiviral factor that also controls MHV68 infection in vivo (Lee, Cool et al, 2009; Lee, Groshong et al, 2009; Steed, Barton et al, 2006; Steed, Buch et al, 2007; Tibbetts, Van Dyk et al, 2002). We have recently shown that IFNγ-mediated restriction of MHV68 replication was attenuated in macrophages lacking type I IFN receptor (Mboko, Rekow et al, 2016). Our published observation in the MHV68 system is consistent with other publications that demonstrated decreased expression of Stat1 in type I IFN deficient cells and constitutive association between IFNAR1 and IFNGR2, indicating an intimate crosstalk between type I and type II IFN signaling networks (Gough, Messina et al, 2010; Takaoka, Mitani et al, 2000).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to the positive role of IRF8 in EBV lytic replication observed in our study, most of the IRFs contribute to anti-viral immunity and block the infection or lytic reactivation of herpesviruses. For example, it was reported that IRF1 restricts gammaherpesvirus replication through IFN-mediated suppression of viral replication [ 73 , 74 , 75 , 76 ]. IRF2 also suppresses gammaherpesvirus replication and reactivation by inhibiting the M2 gene promoter [ 77 ].…”
Section: Discussionmentioning
confidence: 99%
“…To test this hypothesis, we evaluated MHV68 infection in p53 +/+ and p53 -/mice. Although p53 is reportedly an interferon (IFN) stimulated gene that functions in limiting acute viral replication and MHV68 replication is controlled by type I IFNs (37,38), viral loads were equivalent in lungs of p53 -/and WT animals after intranasal inoculation and mortality was not observed during the acute phase of infection ( Fig. S2).…”
Section: Mhv68 Latency Establishment Is Enhanced In P53-deficient Micementioning
confidence: 99%